Digital Innovations in Group Piano Instruction - Chee Hyeon Choi; Chan Kiat Lim (Journal of the Association for Technology in Music Instruction, 2026)
This presentation will explore the transformative impact of integrating web-based digital textbooks into higher education music programs, specifically focusing on group piano curricula. By moving away from traditional paper-based textbooks, this approach leverages interactive, multimedia resources to create a dynamic and engaging learning environment. Attendees will gain insights into how digital textbooks, such as the award-winning eNovative Piano, can enhance students' understanding of musical concepts, foster technical proficiency, and promote a deeper connection between sound, theory, and technique. By attending this session, participants will understand how a multimedia approach in piano education can cultivate adaptability, responsiveness, and creativity, ultimately preparing students for successful careers in a rapidly evolving musical landscape. Higher education music programs mandate music majors to achieve keyboard proficiency, establishing a foundational skill set essential for their musical development. However, as the demands for rapid technological advancements rise, many colleges piano curricula often remain anchored in traditional methodologies, relying heavily on outdated paper-based textbooks. This session demonstrates the transformative benefits of web-based digital textbooks that create a multi-dimensional learning environment, ensuring students are well-prepared for their future careers. Examples will be drawn from an award-winning multimedia group piano text, eNovative Piano.
Keywords: workshop; training; class piano